Relationships Between Memory Impairments and Hippocampal Structure in Patients With Subcortical Ischemic Vascular Disease - He, Miao; Li, Yang; Zhou, Lijing; Li, Yajun; Lei, Ting; Yan, Wei; Song, Jiarui; Chen, Li (Frontiers in Aging Neuroscience, 2022)
Background and Purpose: Patients with subcortical ischemic vascular disease (SIVD) suffer from memory disorders that are thought to be associated with the hippocampus. We aimed to explore changesin hippocampal subfields and the relationship between different hippocampal subfield volumes and different types of memory dysfunction in SIVD patients. Methods: A total of 77 SIVD patients with cognitive impairment (SIVD-CI, n = 39) or normal cognition (HC-SIVD, n = 38) and 41 matched healthy controls (HCs) were included in this study. Memory function was measured in all subjects, and structural magnetic resonance imaging (MRI) was performed. Then, the hippocampus was segmented and measured by FreeSurfer 6.0 software. One-way ANOVA was used to compare the volume of hippocampal subfields among the three groups while controlling for age, sex, education and intracranial volume (ICV). Then, post hoc ttests were used to evaluate differences between each pair of groups. Finally, correlations between significantly different hippocampal subfield volumes and memory scores were tested in SIVD patients. Results: Almost all hippocampal subfields were significantly different among the three groups except for the bilateral hippocampal fissure (p = 0.366, p = 0.086, respectively.) and left parasubiculum (p = 0.166). Furthermore, the SIVD-CI patients showed smaller volumes in the right subiculum (p < 0.001), CA1 (p = 0.002), presubiculum (p = 0.002) and molecular layer of the hippocampus (p = 0.017) than the HC-SIVD patients. In addition, right subiculum volumes were positively related to Rey’s Auditory Verbal Learning Test (RAVLT) word recognition (r = 0.230, p = 0.050), reverse digit span test (R-DST) (r = 0.326, p = 0.005) and Rey–Osterrieth Complex Figure Test (ROCF) immediate recall (r = 0.247, p = 0.035) scores, right CA1 volumes were positively correlated with RAVLT word recognition (r = 0.261, p = 0.026), and right presubiculum volumes showed positive relationships with R-DST (r = 0.254, p = 0.030) and ROCF immediate recall (r = 0.242, p = 0.039) scores. Conclusions: SIVD might lead to general reductions in volume in multiple hippocampal subfields. However, SIVD-CI patients showed atrophy in specific subfields, which might be associated with memory deficits.